Effects of the dietary protein-to-energy ratio on the growth performance, body composition, and health status of large-sized grass carp, Ctenopharyngodon idella - Liao, Zhangbin; Wang, Lei; Yun, Biao; Dong, Xiaolin; Niu, Fengchi; Wang, Jian; Qian, Xueqiao; Hua, Xueming (Frontiers in Physiology, 2025)
A 56-day feeding trial was performed to investigate the effects of the dietary protein-to-energy (P/E) ratio on the growth performance, body composition, and health status of large-sized grass carp, Ctenopharyngodon idella. The fish (initial body weight 2,200.4 ± 79.3 g) were randomly fed one of the six isolipidic and isoenergetic diets (gross energy 10 kJ/g), which were formulated with various P/E ratios (21.7 mg/kJ, 23.7 mg/kJ, 24.9 mg/kJ, 27.1 mg/kJ, 29.2 mg/kJ, and 31.5 mg/kJ) and named P/E 21.7, P/E 23.7, P/E 24.9, P/E 27.1, P/E 29.2 mg/kJ and P/E 31.5, respectively. After the feeding trial, the best growth performance was observed in the P/E 29.2 group, which had the highest weight gain. In addition, fish fed the optimal P/E diet exhibited a superior health status in terms of tissue histology and biochemical analyses of serum and liver. The liver transcriptome assay revealed that a suitable P/E ratio potentially enhances growth performance and immune function by modulating the AMPK signaling pathway, the Ras signaling pathway, and arachidonic acid metabolism, along with affecting rRNA synthesis by regulating ribosome biogenesis gene expression in eukaryotes. Based on the second-order polynomial regression analysis of the growth performance and health status against P/E, the optimal P/E range was found to be 27.36–28.93.